Monitoraggio del reclutamento di anguilla (Anguilla anguilla L. 1758) tramite osservatori. - CICCOTTI, ELEONORA; Monfrinotti, M; Furlani, A; CATAUDELLA, STEFANO (country:IT, 2004)
European eel (Anguilla anguilla L. 1758) is recognised as a international marine species and a shared resource among European and Mediterranean countries. For this species major problems exist, in relation to a continent-wide decline in recruitment observed in the course of the last decades, and to a contraction in fisheries that capture adult eel. In the present paper a monitoring of eel recruitment in Italy is presented, carried out within resource assessment projects of the MIPAF (Ministero per le Politiche Agricole e Forestali). A methodology has been purposely set up based on eel fisheries in the three sites: the river Tiber estuary, the river Marta estuary, the river Garigliano estuary (Latin Central Italy). A fourth site has been selected, where monitoring is carried out by a fishery independent method, i.e. a glass eel trapping ladder to the Monaci coastal lagoon of the Pontinian coastal lakes (Circeo National Park). A progressive declining trend is evident for glass eel recruitment in all sampling sites. These results are in accordance with what observed elsewhere in Europe.